PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan LQ-45 di Bursa Efek Indonesia Tahun 2016-2018) - Luthfina Nurin Shabrina; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2020)
This study aims to examine the effect of intellectual capital on corporate financial performance. The components of intellectual capital used are the efficiency of human capital /HCE, structural capital efficiency/SCE, and capital employed efficiency/CEE. Indicators of the corporate financial performance used are return on assets (ROA) and asset turnover (ATO). This study was conducted using a documentation study with secondary data. The analytical method in this study is a quantitative approach. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) which are included in the LQ45 Index consistently in 2016-2018 and have published financial statements. The results showed that: (1) human capital efficiency / HCE did not affect the rate of return on assets / ROA and had a significant negative effect on asset turnover / ATO. (2) structural capital efficiency/ SCE did not affect the rate of return on assets and asset turnover. (3) capital employed efficiency/ CEE had a significant positive effect on the rate of return on assets and asset turnover.